2019
DOI: 10.1002/jsfa.9925
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy and biochemical changes in silver carp as related to quality of washed mince

Abstract: BACKGROUND Biochemical and protein conformational changes in silver carp occurred during ice storage, affecting the physico‐chemical and textural properties of its washed mince. Fourier‐transform infrared spectroscopy (FTIR) and FT Raman could offer insightful molecular‐level information that could be related to the freshness of fish and textural properties of washed mince. RESULTS The K value increased from 15.8% to 85.0% after 14 days on ice. The surface hydrophobicity of silver carp muscle proteins increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…However, sensory evaluation is subjective and not suitable for routine applications. Microbial analysis and physicochemical methods including the determination of the total volatile basic nitrogen, biogenic amines, thiobarbituric acid reactive substances (TBARS), and peroxide value are commonly used as indicators of fish freshness (Kunyaboon et al., 2019). Although accurate and reliable results can be acquired, these techniques possess several inherent limitations such as invasiveness, labor‐intensive operation, and are not appropriate for field and extensive measurements.…”
Section: Applications Of Rs In Fish Quality and Safetymentioning
confidence: 99%
“…However, sensory evaluation is subjective and not suitable for routine applications. Microbial analysis and physicochemical methods including the determination of the total volatile basic nitrogen, biogenic amines, thiobarbituric acid reactive substances (TBARS), and peroxide value are commonly used as indicators of fish freshness (Kunyaboon et al., 2019). Although accurate and reliable results can be acquired, these techniques possess several inherent limitations such as invasiveness, labor‐intensive operation, and are not appropriate for field and extensive measurements.…”
Section: Applications Of Rs In Fish Quality and Safetymentioning
confidence: 99%
“…The highest gel strength of surimi prepared from just-slaughtered fresh silver carp by comparing gel quality at different periods after death (Lv et al, 2015). Kunyaboon et al (2019) observed that processing silver carp into surimi within 7 days of ice storage resulted in surimi gels with improved yield and texture. Therefore, utilizing fresh raw fish can effectively enhance the surimi gel properties.…”
Section: Introductionmentioning
confidence: 99%
“…Kunyaboon et al. (2019) observed that processing silver carp into surimi within 7 days of ice storage resulted in surimi gels with improved yield and texture. Therefore, utilizing fresh raw fish can effectively enhance the surimi gel properties.…”
Section: Introductionmentioning
confidence: 99%